بعض المهارات الاجتماعية لدى عينة من أطفال ما قبل المدرسة: دراسة في محافظة شمال الشرقية بسلطنة عمان - Mohammed bin Sulayem al-Sawafiyah, J.; Asma' Ab. Rahman, A. (Universiti Sains Islam Malaysia, 2024)
The study aimed at measuring the availability of some social skills in a sample of pre-school children. The problem is that the lack of social skills may lead directly to juvenile delinquency, drop out of school, and relate to forms of atypical behavior and mental health problems in subsequent stages of life. Three social skills were identified for measuring this study (sempathy, communication with others, cooperation), the measure was applied to an equal sample of males and females of (20) pre-school children (4-6 years) from the Snaw School of the Sanaa Prosecution in the state of Al-Madaybi in North Sharqia Governorate. The researcher used a measure of social intelligence in a study of Qatami and Yusuf (2010), which consists of a photographer's scale and a note form for the teacher, After the completion of the scale was answered the questions of the study where the proportion of all children in the overall test was (73.7%), (76.9%), communication with others (71.6%), and cooperation (70%). The researcher recommended the implementation of a program aimed at raising the social skills (empathy, communication with others, cooperation) in pre-school.